Highly enantioselective synthesis of dihydrocoumarin-fused dihydropyrans via the phosphine-catalyzed [4 + 2] annulation of allenones with 3-aroylcoumarins. Issue 22 (13th May 2016) - Han, Xiaoyu; Ni, Huanzhen; Chan, Wai-Lun; Gai, Xikun; Wang, Yongjiang; Lu, Yixin
Abstract : Phosphine-catalyzed [4 + 2] annulation between 3-aroylcoumarins and allenones has been developed. Abstract : Phosphine-catalyzed [4 + 2] annulation between 3-aroylcoumarins and allenones has been developed. In the presence of a dipeptide phosphine catalyst7, dihydrocoumarin-fused dihydropyrans were prepared in high yields and with excellent enantioselectivities.